Efficient and stable all-inorganic perovskite solar cells based on nonstoichiometric CsₓPbI₂Brₓ (x > 1) alloys - Frolova, Lyubov A. (2021)
Here we report a systematic study of all-inorganic perovskite-inspired systems based on CsₓPbI₂Brₓ alloys with x ranging from 0.95 to 4. The identified optimal non-stoichiometric composition Cs₁.₂PbI₂Br₁.₂ delivered the best optoelectronic, structural and photovoltaic characteristics in combination with the improved stability. The elucidated remarkable effect of the Cs₄PbI₂Br₄ impurity phase, serving as a reservoir of CsBr, on the photothermal stability and photovoltaic performance of CsPbI₂Br perovskite films offers a new paradigm in the development of more efficient and stable all-inorganic perovskite solar cells.